A legal approach to whether ai generated content should be protected under copyright - Stransky, Caitlin (University of the Witswatersrand, Johannesburg, 2023)
Currently, there is no clear answer for whether AI-generated content should be protected under copyright law in South Africa and if so, who is the author and who owns the copyright. As AI is growing more advanced and widely used, the potential for confusion grows and thus clarity on the law’s position is important. In this paper, I will examine how AI generates works and compare this to the purpose of copyright law. I will then determine whether granting AI- generated works copyright protection aligns with the purpose of copyright law. Further, I will conduct an analysis on how different countries have dealt with the question of whether AI-generated content should be protected under copyright. This will help pinpoint the factors to consider when answering this question such as the requirement of human authorship, legal or juristic person ownership of the copyright and whether the works are copyrightable. It is important to consider how South Africa’s legal system should approach issues surrounding AI-generated content and copyright. In examining the South African legal position on this question, I will conduct an analysis on the approaches taken by the US, the UK, Germany, Australia, China, and South Africa in relation to AI-generated works and copyright. This range of countries will allow for a greater understanding of the issues, complexities, and factors to consider while answering this question
Submitted in partial fulfilment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg
Keywords: AI-generated content; UCTD; Copyright; Copyright protection; SDG-9: Industry, innovation and infrastructure